PENODAAN AGAMA DI MEDIA SOSIAL DAN DAMPAK HUKUMNYA: KAJIAN LINGUISTIK FORENSIK - Dheni Budiman; Dadang Sudana; ndika Dutha Bachari; Marlia (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
Indonesia is not a religious state, but the state guarantees freedom of religion and every citizen has the right to embrace religion according to their beliefs. This implies that the state is obliged to make regulation to protect its citizens, and prohibit anyone from committing blasphemy. However, in fact practices of intolerance in religion, namely blasphemy are found. The purpose of this research is to find out what lexical meanings appear in blasphemy; knowing the purpose of blasphemy; and uncovering and describing the impact of blasphemy on social media. The method used in this research is a qualitative method with a forensic linguistic study approach. From the results of this reseach, it can be concluded that; 1) the lexical meanings appearing in the research data are grouped into six groups, 2) the purpose of blasphemy on social media is utterances to hate, insult the dignity of religion, 3) the legal impact of blasphemy on social media is by imposing a court judge's verdict on a defendant who is proven to have committed blasphemy on social media.